2019
DOI: 10.1016/j.arth.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Two-State Comparison of Total Joint Arthroplasty Utilization Following Medicaid Expansion

Abstract: BACKGROUND: While Medicaid expansion has improved access to primary care services, its impact on surgical specialty utilization remains unclear. To determine whether Medicaid expansion was associated with increased compared utilization rates of total hip arthroplasty (THA) and total knee arthroplasty (TKA) in Illinois (which expanded Medicaid) relative to Missouri (which did not expand Medicaid). METHODS: Using administrative data sources, we analyzed 374,877 total hospitalizations (236,333 in Illinois and 138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Reflecting this difference, we observed a notably larger shift in Medicaid payer mix after Medicaid expansion (6.0%) than has been shown previously for hip and knee arthroplasty (1.5%). 6 Beyond orthopedic conditions, the impact of Medicaid expansion on elective spine surgical care should be interpreted within the context of the broader surgical and economic literature. We observed an overall 17% increase in elective spine surgical volume, similar to rate changes found in studies that evaluated major general surgery procedures such as gastric bypass surgery (8%), paraesophageal hernia or reflux disease surgery (17%), cancer surgical procedures (12%), hernia repair (16%), and vascular surgery (20%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reflecting this difference, we observed a notably larger shift in Medicaid payer mix after Medicaid expansion (6.0%) than has been shown previously for hip and knee arthroplasty (1.5%). 6 Beyond orthopedic conditions, the impact of Medicaid expansion on elective spine surgical care should be interpreted within the context of the broader surgical and economic literature. We observed an overall 17% increase in elective spine surgical volume, similar to rate changes found in studies that evaluated major general surgery procedures such as gastric bypass surgery (8%), paraesophageal hernia or reflux disease surgery (17%), cancer surgical procedures (12%), hernia repair (16%), and vascular surgery (20%).…”
Section: Discussionmentioning
confidence: 99%
“…38,42,43 Finally, previous evidence suggests that the shift to ambulatory surgical procedures has occurred in similar proportions across states and geographic regions, making a differential impact associated with Medicaid expansion status unlikely. 44,45 Another limitation is that despite the inclusion of a larger sample of states than many comparable studies, [6][7][8] our sample size still limited our ability to test for heterogeneity in effects across states, such as variations related to the expansion strategies of individual states. 17 Finally, the study data set did not allow us to investigate the exact mechanisms that led to the observed changes, such as increased imaging and referral rates by primary care physicians versus changes in decision-making among spine surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there can be historical, cultural, political, and demographic differences among states coupled with individual level factors such as personal experience using health insurance, access to primary care, and levels of health literacy (McCullough & Dalstrom, 2018; Singh & Wilk, 2019), which might partially explain the differences in outcomes. Finally, there is not a consensus in how access to healthcare is measured with some researchers focusing on reduced financial barriers (Miller & Wherry, 2017; Sommers et al., 2016), unmet needs (Benitez et al., 2018), use (Dy et al., 2019), or ability to access care when needed (Singh & Wilk, 2019).…”
Section: Introductionmentioning
confidence: 99%